Differential behavioral and neuroendocrine effects of repeated nicotine in adolescent and adult rats - Cruz, F. C.; DeLucia, R.; Planeta, Cleopatra da Silva [UNESP] (Elsevier B.V., 2005)
Despite the high prevalence of tobacco abuse among adolescents, the neurobiology of nicotine addiction has been studied mainly in adult animals. Repeated administration of this drug to adult rats induces behavioral sensitization. Nicotine activates the HPA axis in adult rats as measured by drug-induced increases in ACTH and corticosterone. Both behavioral sensitization and corticosterone are implicated in drug addiction. We examined the expression of behavioral sensitization induced by nicotine as well as the changes in corticosterone levels after repeated injections of nicotine in adolescent and adult animals. Adolescent and adult rats received subcutaneous (s.c.) injections of saline or 0.4 mg/kg of nicotine once daily for 7 days. Three days after the last injection animals were challenged with saline or nicotine (0.4 mg/kg; s.c.). Nicotine-induced locomotion was recorded in an activity cage. Trunk blood samples were collected in a subset of adolescent and adult rats and plasma corticosterone levels were determined by radioimmunoassay. Adult, but not adolescent, rats expressed behavioral sensitization. Pretreatment with nicotine abolished corticosterone-activating effect of this drug only in adult animals, indicating the development of tolerance at this age. Our results provide evidence that adolescent rats exposed to repeated nicotine display behavioral and neuroendocrine adaptations distinct from that observed in adult animals. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: nicotine; behavioral sensitization; corticosterone; locomotor activity; adult; adolescent; rat